2017
DOI: 10.1111/cpf.12468
|View full text |Cite
|
Sign up to set email alerts
|

Estimated peak functional capacity: an accurate method for assessing change in peak oxygen consumption after cardiac rehabilitation?

Abstract: Change in estimated VO derived from the ACSM leg cycling equation is not an accurate surrogate for directly determined changes in VO . Our findings show poor agreement between estimates of VO and directly determined VO . Applying estimates of VO to determine CRF change may over-estimate the efficacy of CR and lead to a different interpretation of study findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A UK multi-centre study including 950 patients reported that estimated VȮ 2peak increased by as little as 1.8 ml•kg• −1 min −1 (0.52 METs) following six to eight weeks (6 to 16 sessions) of exercise-based CR [13]. We have shown that estimated VȮ 2peak over-estimates measured changes in VȮ 2peak by 0.7 ml•kg• −1 min −1 (−4•7 to 5•9 ml•kg• −1 min −1 ) [18]. Thus, improvements in peak aerobic fitness resulting from routine exercise-based CR in the UK may be minimal.…”
Section: Introductionmentioning
confidence: 79%
“…A UK multi-centre study including 950 patients reported that estimated VȮ 2peak increased by as little as 1.8 ml•kg• −1 min −1 (0.52 METs) following six to eight weeks (6 to 16 sessions) of exercise-based CR [13]. We have shown that estimated VȮ 2peak over-estimates measured changes in VȮ 2peak by 0.7 ml•kg• −1 min −1 (−4•7 to 5•9 ml•kg• −1 min −1 ) [18]. Thus, improvements in peak aerobic fitness resulting from routine exercise-based CR in the UK may be minimal.…”
Section: Introductionmentioning
confidence: 79%
“…Field-tests may provide a useful indication of a patients' aerobic fitness, the presence of a 'normal response' to exercise, and provide information that can be used to inform exercise prescription. However, estimating VO 2peak may be inaccurate, particularly when measuring changes in VO 2peak after exercise-based CR [90]. Maximal cycle ergometry data from patients with CHD, collected by our group, showed that estimating changes in VO 2peak resulted in significant measurement error, when compared to directly determined VO 2peak (limits or agreement − 4.7 to 5.9 ml • kg 1 • min).…”
Section: Frequencymentioning
confidence: 86%
“…Applying estimates of VO 2peak to determine CRF change may over-estimate the efficacy of CR and lead to a different interpretation of study findings. [ 23 ] There are very few centres in the UK which have adopted maximal cardiopulmonary exercise testing as routine for evaluating clinical populations and prescribing individualised exercise training loads. The outcomes of the CARE CR trial, which used criterion exercise testing methods to evaluate the effectiveness of a UK CR programme recently showed that in 70 patients with coronary heart disease, there was no changes in directly determined at any time point following an 8-week CR programme.…”
Section: Discussionmentioning
confidence: 99%